2014
DOI: 10.7883/yoken.67.464
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective, Hospital-Based Study to Determine the Incidence of Rotavirus Hospitalizations among Children Less than 5 Years of Age over a 10-Year Period (2001^|^ndash;2011) in Akita Prefecture, Japan

Abstract: SUMMARY: Rotavirus is the most common cause of severe gastroenteritis in children worldwide. This retrospective, cross-sectional study was undertaken in a sentinel hospital that provides the only pediatric beds for the local population with an average of 4,400 children aged <5 years and determined the incidence of rotavirus hospitalizations. Medical charts that recorded acute gastroenteritis cases occurring in children aged <5 years living in the cites of Yuri-Honjo or Nikaho, Akita, Japan between 2001 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Thus, in 2009 the World Health Organization (WHO) recommended that rotavirus vaccine should be incorporated in the infant immunization schedule of every country in the world ( http://www.who.int/mediacentre/news/releases/2009/rotavirus_vaccines_20090605/en/ ). Although the number of deaths due to rotavirus gastroenteritis is small in Japan, the incidence rate of rotavirus hospitalisations was reported to range from 2.8 to 13.7 per 1000 child-years among children less than 5 years of age [ 2 7 ], imposing a substantial burden to the healthcare system in the country.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in 2009 the World Health Organization (WHO) recommended that rotavirus vaccine should be incorporated in the infant immunization schedule of every country in the world ( http://www.who.int/mediacentre/news/releases/2009/rotavirus_vaccines_20090605/en/ ). Although the number of deaths due to rotavirus gastroenteritis is small in Japan, the incidence rate of rotavirus hospitalisations was reported to range from 2.8 to 13.7 per 1000 child-years among children less than 5 years of age [ 2 7 ], imposing a substantial burden to the healthcare system in the country.…”
Section: Introductionmentioning
confidence: 99%
“…In a 10-year retrospective study, Kinoshita et al (11) reported that the lowest incidence rate was 6.8 cases per 1,000 child-years, while the highest was 20.7 cases per 1,000 child-years. While the cause of such yearly variation is not known, different circulating strains are often suspected.…”
Section: Discussionmentioning
confidence: 99%
“…47 Hospitalisation incidence rates were taken from a 10-year retrospective, hospital-based study. 48 Causal relationship of encephalitis/ encephalopathy with rotavirus infection has been putative since à After recovery, individuals may proceed to the following health status: "One previous infection", "Two previous infection" or "Immunised".…”
Section: Annual Incidence Rates and Case Fatality Ratesmentioning
confidence: 99%